THE TAMILS’ EARTHEN OCCUPATIONS AS SHOWN BY THE VENPAMALAI - J. Arulmarcia (ShodhKosh: Journal of Visual and Performing Arts, 2025)
It was considered a tradition for the Venpamalai to mention the king, leader, or patrons who ruled the Tamil land and to sing about their valor, victory, gifts, and indestructibility. The Venpamalai says that conquering the country, attracting the gods, and rescuing them are valor and victory. Apart from that, they were happy to think about the victories they achieved in the soil and in soil-related games. All these victories highlight the soil and the earth-related occupations. It also explains how all the earth-related occupations did not affect the natural environment in any way and how harmless activities were carried out.